2017
DOI: 10.2528/pierc17011101
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Perfect Metamaterial Absorber on Thin Substrate for X-Band and Ku-Band Applications

Abstract: Abstract-A broadband Perfect Metamaterial Absorber (PMA) on FR-4 Epoxy substrate for X-band and Ku-Band applications is proposed. The unit cell structure is composed of rectangular patches of appropriate shapes and orientation on top of the metal-backed dielectric substrate having a thickness of 2.7 mm (0.16λ L ). The relative absorption bandwidth is 79% (more than 85% absorption) covering the entire X-band and the Ku-Band of the microwave frequencies. The surface current distributions of the top and bottom pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Most of these imaging techniques employ MAs in their imaging systems to control the EM process such as absorption, polarization, and spectral bandwidth. Selective multi-frequency sensor [81], healthcare sensor [125], thermal sensor [129], plasmonic sensor etc. also employ absorbers.…”
Section: Applicationsmentioning
confidence: 99%
“…Most of these imaging techniques employ MAs in their imaging systems to control the EM process such as absorption, polarization, and spectral bandwidth. Selective multi-frequency sensor [81], healthcare sensor [125], thermal sensor [129], plasmonic sensor etc. also employ absorbers.…”
Section: Applicationsmentioning
confidence: 99%
“…Moreover, the design structure provides high absorption peaks of 99.64% at 8.08 GHz and 99.95% at 11.41 GHz, respectively. It is observed that the absorption of the proposed design is better than the suggested metamaterials unit cells in [12][13][14][17][18][19][20][21][22][23][24][25]. To determine the absorption parameters, the Computer Simulation Technology (CST) microwave studio suite simulator 2015 is used.…”
Section: Design Numerical Simulation and Experimentsmentioning
confidence: 99%
“…Absorption of the design structure for number of metallic resonators. [17] S-shape 20 × 20 S-, X-, Ku-band 55.00 2017 Sen et al [25] L-shape 9 × 9 X-, Ku-band 95.00 2017 Mahmood et al [24] Modified S-shape 16 × 16 X-band 90.00 2017 Proposed PMA Octagonal shape 10 × 10 X-band 98.97 -…”
Section: Analysis Of Design Structure With Resonator's Numbermentioning
confidence: 99%
“…However, the bandwidths of these absorbers are still narrow [11,23,24]. Some works were done with a very small size of unit cells, but they compromised the bandwidth [25][26][27]. Many researchers are working in this particular field to design a perfect MM absorber with broad band and polarization-insensitive features [28] to employ in stealth and radar systems.…”
Section: Introductionmentioning
confidence: 99%